Physiological Characteristics and Environment Adaptability of Reef-Building Corals at the Wuzhizhou Island of South China Sea - Xu, Huili; Feng, Boxuan; Xie, Minrui; Ren, Yuxiao; Xia, Jingquan; Zhang, Yu; Wang, Aimin; Li, Xiubao (Frontiers in Physiology, 2020)
The health of coral reef has declined significantly around the world due to the impact of human activities and natural environment changes, and corals have to develop effective resistance mechanisms to survive. In this study, we examined the physiological characteristics and Symbiodiniaceae types of four dominant scleractinian corals in the reefs at the Wuzhizhou Island (WZZ) in South China Sea. The water environmental conditions are complex on the north side of WZZ due to regional geography and tourism development, and all corals had their unique physiological conditions and Symbiodiniaceae types. For all corals of this study, the rETRmax and protein content were significantly lower and the SOD enzyme activity was significantly higher in the north than in the south. Interestingly, ITS2 genotyping showed that Galaxea fascicularis contained dominant Symbiodiniaceae either genotype C21 or D1a depending on the regional environmental stress, and had stronger heterotrophy than the other three coral species. In addition, the light use efficiency of the dominant Symbiodiniaceae type C1 for Pocillopora verrucosa was significantly lower in the north and the half saturating irradiance was stable. Besides, Montipora truncata and P. verrucosa increased their density of the symbiotic zooxanthella C1 in the north to offset the decline of photosynthetic efficiency and thus supply energy. For Porites lutea and G. fascicularis, their half saturating irradiance declined sharply in the north, where P. lutea resorted to heterotrophic feeding to balance the energy budget when the number of zooxanthellas fell short and G. fascicularis reduced its energy reserve significantly when the energy source was limited. We thus demonstrated the differences in the physiological responses and energy metabolism strategies between the zooxanthella and the host coral of the four reef-building coral species under the stress of complex water environment on the north side of WZZ. The corals were found to cope with natural and anthropogenic stressors by adjusting the nutrient input sources and the energy structure metabolism of coral hosts or adapting to more sustainable relationship with Symbiodiniaceae clades. The corals exhibited their capacity against long-term disturbances by developing their own successful resistance mechanisms at symbiotic relationship and energy metabolism level.